Interfaith Dialogue and a Lotus Practitioner: Yamada Etai, the "Lotus Sutra", and the Religious Summit Meeting on Mt. Hiei - Covell, Stephen Grover (Japanese journal of religious studies, 2014)
This article is an examination of Yamada Etai, the 253rd head priest (zasu) of the Tendai denomination and his efforts to host the Religious Summit Meeting on Mt. Hiei. Following an in-depth analysis of Yamada's understanding of the Lotus Sutra, especially as it relates to interfaith outreach, Yamada's efforts to reshape contemporary Tendai Buddhism through a focus on compassionate service and salvation are examined in light of his efforts to put on a large-scale international interfaith meeting.